Cervical cancer screening among homeless women of New York City shelters - Asgary, Ramin (Matern Child Health J, 2016)
INTRODUCTION: Homeless persons have minimal opportunities to complete recommended cancer screening. The rates and predictors of cervical cancer screening are understudied among homeless women in the US. METHODS: We enrolled 297 homeless women 21–65 years old residing in 6 major New York City shelters from 2012 to 2014. We used a validated national survey to determine the proportion and predictors of cervical cancer screening using cytology (Pap test). RESULTS: Mean age was 44.72 (±11.96) years. Majority was Black, heterosexual, single, with high school or lower education; 50.9% were smokers and 41.7% were homeless more than a year. Despite a 76.5% proportion of self-reported Pap test within the past 3 years, 65% of women assumed their Pap test results were normal or did not get proper follow up after abnormal results. Forty-five-point-nine percent of women did not know about frequency of Pap test or causes of cervical cancer. Lower proportion of up-to-date Pap test was associated with lack of knowledge of recommended Pap test frequency (p<0.01) and relationship between HPV and an abnormal Pap test (p<0.01). CONCLUSIONS: Self-reported Pap testing in homeless women was similar to a national sample. However, the majority of women surveyed were not aware of their results, received limited if any follow up and had significant education gaps about cervical cancer screening. We recommend improved counseling and patient education, patient navigators to close screening loops, and consideration of alternative test-and-treat modalities to improve effective screening.